2015
DOI: 10.1039/c4cc06165a
|View full text |Cite
|
Sign up to set email alerts
|

The coaction of tonic and phasic dopamine dynamics

Abstract: Tonic neurochemical dopamine activity underlies many brain functions; however a consensus on this important concentration has not yet been reached. In this work, we introduce in vivo fast-scan controlled-adsorption voltammetry to report tonic dopamine concentrations (90 ± 9 nM) and the dopamine diffusion coefficient (1.05 ± 0.09 ×10−6 cm2/s) in the mouse brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
104
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 43 publications
13
104
1
Order By: Relevance
“…This technique provides a limit of detection ( < 10 nM dopamine) sufficient for in vivo use and can be alternated with normal FSCV measurements to monitor rapid dopamine changes at the same microelectrode. An initial study employing FSCAV in the mouse striatum reported basal dopamine levels to be close to 100 nM (98), a value consistent with the concentration range suggested by past studies (8, 9194). …”
Section: Novel Applicationssupporting
confidence: 83%
“…This technique provides a limit of detection ( < 10 nM dopamine) sufficient for in vivo use and can be alternated with normal FSCV measurements to monitor rapid dopamine changes at the same microelectrode. An initial study employing FSCAV in the mouse striatum reported basal dopamine levels to be close to 100 nM (98), a value consistent with the concentration range suggested by past studies (8, 9194). …”
Section: Novel Applicationssupporting
confidence: 83%
“…18,2532 Figure 3 shows CVs collected in vitro from these different species at concentrations that mimic a range of reported or predicted physiological values. 4,5,16,24,29,3339 …”
Section: Resultsmentioning
confidence: 99%
“…15 Our studies revealed a fundamental coaction between evoked and ambient dopamine. 16 Here, we orient this method toward serotonin.…”
mentioning
confidence: 99%
“…Recent studies have exploited the catecholamine adsorption properties of carbon fiber microelectrodes (CFM), to estimate basal concentrations of neurochemicals. [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%